SEDIMENTOLOGI BATUGAMPING FORMASI RAJAMANDALA DI LINTASAN SANGHYANG, CITATAH, BANDUNG BARAT - Sigit Maryanto (Jurnal Geologi dan Sumberdaya Mineral, 2012)
The limestones of the Oligo-Miocene Rajamandala Formation cropped out at Sanghyang section, West Bandung District. Detailed stratigraphic section measured out along this 2.5 km section to predict the development of their depositional environments. This Rajamandala Formation having measured of 180 m thickness, and composed of boundstone, rudstone, grainstone, packstone, wackestone, and comm only deposited at regression basin. This Oligo-Miocene formation was situated at the southern part of the Eurasian continent foreland basin. The depositional environment of [his formation was initiated in core-reef to fore-reef slope facies. The deposition becomes interbeded of fore-reef slope to reef-flank facies with several core-reef facies. Due to regression event, the depositional environment change and jinalized by slope and shelf edges facies of carbonate platform.Keywords: Core-reef, fore-reef, reef-flank, slope and shelf edge.